Opinions of Primary School Teachers in Relation to Effectiveness and Applicability of Design Skill Workshops - GÜNDÜZ, GÜLTEN FERYAL (Abdullah Kuzu, 2020)
General purpose of this research is to determine the opinions of primary school teachers on the effectiveness and applicability of the studies conducted in relation to Design Skills Workshops (TBA). The participants of the study, designed according to the phenomenology research model, are 20 teachers who work in one of the primary schools that are pilot in the use of TBAs. Research data were collected by using a semi-structured interview form. According to the findings, generally the teachers consider the use of TBAs in education as a positive development for the Turkish education system, but they think that it is difficult to apply them in all schools throughout the country. While almost all of the teachers consider that the training given by the Istanbul Provincial Directorate of National Education for the use of TBAs is insufficient, all of the teachers found the studies of the school administration for the use of TBAs sufficient. Teachers actively use all the workshops in the school, except for the wood, garden and animal care workshops, in almost all lessons. Teachers stated that the use of TBAs mostly enabled students to develop collaborative learning, creative thinking and hand skills. According to the teachers, the use of TBAs enables teachers to associate the lessons with each other more, to do more research and to prepare more detailed lesson plans while performing their teaching. According to the results, most of the teachers do not consider that TBAs are applicable throughout the country because of the crowded class sizes, the teachers’ not having enough knowledge about using TBAs, and the physical conditions’ not being sufficient. Among the proposals made by teachers regarding arrangements to be made in relation to TBAs before disseminating them throughout the country, having collaboration among teachers responsible from design skills workshops and among these teachers and class teachers comes at the forefront. Providing longer-term training for teachers on how TBAs should be used is another most recommended issue.
İlkokul Öğretmenlerinin Tasarım Beceri atölyelerinin Etkililiğine Ve Uygulanabilirliğine Yönelik Görüşleri
Keywords: Primary School Teachers; Turkey's Education Vision 2023; Design Skill Workshops